Pedogênese de um solo calcário e alterações de seus atributos em resposta a irrigação. - Costa, Priscilla Alves da (2012)
Water is a priceless natural resource. More than an essential input to production is a strategic resource for economic development. The semiarid region, as well as the rest of the world, suffer more with climate change associated with global warming. These climate changes have impacts on both supply and demand for water in this region. In northeastern Brazil, where there is an uneven distribution of rainfall, agricultural production is substantially improved through the use of irrigation. The adoption of the use of irrigation in these semiarid regions leads to changes in soil moisture regime and may even change its properties and processes. The objective of this study was to investigate the effects during 23 years of irrigation on calcareous soils in semiarid Ceará, with emphasis on the study of pedogenetic changes provided by this practice. The areas chosen for study are located in Chapada do Apodi located in the city of Limoeiro do Norte - Ce. 8 amostrgens were performed in each area (in the irrigated area and the area outside and adjacent to the pivot). Subsequently, in each of the areas, trenches were opened to perform the morphological descriptions and collected soil samples for physical characterization, chemical, mineralogical and micromorphological. The results indicate significant differences have occurred in the irrigated area compared to non-irrigated area, and verified the increased dissolution of CaCO3 and increased levels of calcium, sodium and phosphorus. Furthermore, the flooded soil has changed its physical characteristics, and found an increase in density of particles decreased permeability of the soil air and the formation of pores less continuous. The analysis results showed that the profiles of 23 years of irrigation had effect on irrigated soil, making it more evolved in comparison to non-irrigated, it was verified by the results obtained in morphology with increasing soil thickness in physics with a lower silt / clay ratio and higher clay content in soil, mineralogy with evidence of increased neoformation of kaolinite and interstratified minerals, in micromorphology with the highest degree of pedalidade. The irrigated soil was classified as Chernosol by presenting chernozênico horizon followed by an incipient B horizon and possess high activity clay.